A Corpus-Based Study of the Metaphor Silence in Lahore, I Am Coming - Sadaf Iftikhar; Tehseen Zahra; Ajmal Gulzar (NUST Journal of Social Sciences and Humanities)
Thought and logic are the underlying foundations of language in use. One of the representations of language in use is poetry; a widely used literary genre throughout the world. The current study aims to identify instances of silence as a metaphorical expression in Akhtar’s (2017) Lahore, I Am Coming. The metaphorical expressions are mapped into source domain and target domain by deciphering the underlying meaning (theme) of the keyword in context (KWIC) silence. The qualitative and interpretive research design is used with Lakoff and Johnson’s (1980) Conceptual Metaphor Theory to develop the linguistic metaphor of silence at the conceptual level via thematic study. The findings of the study reveal that silence is significantly used as a metaphorical expression to express several key themes such as human relationships (love), colonialism and imperialism, and representation of females. The conceptual metaphors of silence are used to convey unified themes of loss, love, and language. Future researchers can conduct a linguistic analysis, specifically cognitive-linguistic analysis of Akhtar’s (2017) Lahore, “I Am Coming” to study the creative use of the figurative use of language.